The economic performance analysis of organic farms in the Czech Republic - Ivana BROŽOVÁ (Agricultural Economics (AGRICECON), 2011)
The research presented in the paper was aimed at analyzing the economic performance of organic farms in the Czech Republic and at evaluating their operation in variants (i.e. including or excluding subsidies). The research was targeted solely at legal entities due to a limited data base. The performance of organic farms (individual kinds of legal entities) was compared by regions with the agricultural enterprises farming conventionally. The organic farms economic profit was as well assessed in relation to their field of activity. Based on the analysis made, the economic situation is more favourable for the organically farming enterprises. Their economic results are actively influenced by subsidies without which an absolute majority of enterprises would be operating at a loss. (When including subsidies in the yields, 84.9% farms of the sample were profitable. On the other hand, while excluding subsidies, 95.7% of the enterprises were loss-making.) Economic success of the farms is influenced - together with subsidies - by the natural and climatic conditions as well as and by their field of activities. The enterprises farming permanent grassland (solely or in combination with a different culture) prevail. A lower intensity of this farming is reflected in the more favourable economic results.